Potential Properties of Plant Sprout Extracts on Amyloid β - Mizue Okada; Yoshinori Okada (Biochemistry Research International)
The aim of this study is to examine the amyloid β (Aβ) inhibition mechanism of plant sprouts’ aqueous extracts (PSAE). In this study, we screened the effects of five plant sprouts’ extracts on Aβ (1–42) structure modification using gel electrophoresis. In PSAE, no band of Aβ monomer was recognized in Japanese butterbur. Similarly, the Aβ monomer band became light in buckwheat, red cabbage, broccoli, and brussels. The neuroprotective effects of PSAE were evaluated by measuring levels of Aβ in mixtures (Aβ  and PSAE) with Aβ ELISA assay. The treatment with PSAE decreased Aβ levels. The results indicated that the levels of red cabbage, Japanese butterbur, and broccoli were 9.6, 28.0, and 44.0%, respectively. The lowest value was observed with buckwheat. Furthermore, we carried out a Congo Red (CR) and Aβ binding experiment of PSAE to confirm the modification mechanism of PSAE. The correlation coefficient for the absorption spectrum peak of CR was found to be bigger than 0.8 (r=0.882) which proved that the Aβ levels could be attributed to the peak of CR. In conclusion, we demonstrated that treatment with PSAE effectively decreases Aβ concentration. Thus, the mechanism that decreased the Aβ levels may be modification by PSAE.